Strategi Public Relations Digital Organisasi Sektimuda dalam Mengkonstruksi Identitas Petani Muda Melalui Platform Instagram - Yassar Hayyan Amaytama; Zayyin Abdul Quddus (Jayapangus Press, 2025)
Indonesia's agricultural sector faces a regeneration crisis due to the negative stigma that farming is dirty and unpromising. Sekolah Tani Muda (Sektimuda) responds to this by utilizing Instagram to deconstruct this image. This study aims to analyze Sektimuda's digital Public Relations strategy in constructing the identity of young farmers using the R-A-C-E (Research, Action, Communication, Evaluation) model. Using a qualitative case study method, data were collected through in-depth interviews with social media managers and content observation, then analyzed using the Miles and Huberman model. The results show that Sektimuda implements an adaptive strategy where the Research and Action phases focus on mapping stigma to position Instagram as a narrative battlefield. In the Communication phase, rather than centralized aesthetics, Sektimuda employs a spirit of equality through communal visuals and ideological narratives regarding independence and systemic awareness, rather than just technical farming. The Evaluation phase confirms that vanity metrics (likes/views) are disregarded in favor of the primary KPI of real participation (class registrants), with audience feedback serving as a mechanism for content improvement. It is concluded that Sektimuda's digital PR strategy successfully reconstructs the farmer identity from physical laborers to politically conscious intellectual subjects. This implies that youth organizations can effectively build image and public participation by prioritizing authentic ideological messages and dialogic interaction over mere visual aesthetics.